2020
DOI: 10.31557/apjcp.2020.21.3.845
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care in the Health System of Iran: A Review of the Present Status and the Future Challenges

Abstract: Based on Bloomberg's ranking, Iran has been ranked as the 45 th country in the world in terms of effective health system. The Ministry of Health and Medical Education (MOHME) is responsible for the health stewardship and centralized sovereignty. The activities of this ministry have shown improved health status over the past few decades (Rafiei et al., 2015). Nevertheless, the health system of Iran faces major challenges. The major challenges of the health system of Iran include increasing the elderly populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 18 publications
(13 reference statements)
2
23
0
Order By: Relevance
“…In regard with academic education and the expected skills and competencies, according to the experts, the development of the specialized discipline, the fellowship course, and master’s degree program for hospice care are not mandatory. Holding short-term hospice care skill training courses to provide specialist manpower obtained higher feasibility, which is in line with the policies adopted in other countries around the world and even in other Middle Eastern countries ( Barasteh et al, 2020 ).…”
Section: Discussionsupporting
confidence: 66%
“…In regard with academic education and the expected skills and competencies, according to the experts, the development of the specialized discipline, the fellowship course, and master’s degree program for hospice care are not mandatory. Holding short-term hospice care skill training courses to provide specialist manpower obtained higher feasibility, which is in line with the policies adopted in other countries around the world and even in other Middle Eastern countries ( Barasteh et al, 2020 ).…”
Section: Discussionsupporting
confidence: 66%
“…The important components and findings of final included articles are presented in Table 2 . Results of the study showed that included studies had a focus on different patients/participants including cancer,[ 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] hemodialysis,[ 45 ] heart failure,[ 46 47 ] chronic disease,[ 48 ] chronic pain,[ 49 ] and with anonymous groups. [ 50 51 52 53 54 55 ] Several provinces/cities were engaged in the studies including Tehran,[ 12 13 14 15 17 20 21 24 25 26 29 30 31 32 33 34 35 37 39 40 41 42 43 48 , 51 , 52 Isfahan,[ 22 27 28 …”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] Majority of studies had quantitative approach, including interventional,[ 17 18 19 22 23 29 31 33 35 44 47 49 54 ] descriptive,[ 20 39 41 42 50 53 ] and correlational-analytical. [ 37 45 46 51 ] This was then followed by qualitative[ 12 13 14 15 16 21 24 25 26 27 30 32 34 36 40 43 48 52 ] and mixed methods. [ 28 38 55 ] In quantitative interventional PC studies, a range of medical-surgical,[ 17 18 19 23 29 31 33 37 ] educational,[ 44 49 54 ] and psycho-spiritual[ 22 35 ] managements were used as an independent variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this program, all levels of health care services can be offered as a special package with different age groups and health conditions. They can be provided in 24 hours/7 days or intermittently for patients at home (Barasteh et al, 2020). In Naylor's model the home health care nurse, has a supportive role and performs home visits to ensure the continuity of care after the discharge (Naylor, 2004).…”
Section: Discussionmentioning
confidence: 99%